Modelling Intestinal Glucose Absorption using Continuous Glucose Monitor Data. Issue 20 (2015) - Dickson, J.; Signal, M.; Harris, D.; Marics, G.; Weston, P.; Harding, J.; Tóth-Heyn, P.; Hómlok, J.; Benyó, B.; Chase, J.G.
Abstract: Hyperglycaemia is a common complication of prematurity in neonatal intensive care. Physiological model-based protocols offer great potential for allowing patient-specific insulin therapy. One aspect of such models is the appearance of glucose in the bloodstream from enteral feeds. A two compartment model is used to capture glucose transport in the stomach and gut. The rate of transfer of glucose from the stomach compartment to the gut can be determined from gastric emptying, which in term infants can be modelled with a half life of around 20 minutes (d1 =0.035 min −1 ). In premature infants gastric emptying is slower, so can be modelled with a half life of around 40 minutes (d1 =0.017 min −1 ). CGM data showing the appearance of glucose from enteral feeds in term and premature infants was used to estimate the rate constant for glucose absorption from the gut to the bloodstream. This absorption rate constant was found to vary between infants and over time. The median absorption constant was found to be d2 =0.014 min −1, which corresponds to an absorption half life of 50 minutes. If fitting error that fell within blood glucose measurement error was considered, the range of possible absorption half lives of absorption was 30-63 minutes.